2022
DOI: 10.1128/mbio.02510-22
|View full text |Cite
|
Sign up to set email alerts
|

MIR155HG Plays a Bivalent Role in Regulating Innate Antiviral Immunity by Encoding Long Noncoding RNA-155 and microRNA-155-5p

Abstract: Here, we found that lncRNA-155KO mice lacking most of the lncRNA-155 sequences along with pre-miRNA-155, were more susceptible to influenza virus or pseudorabies virus infection than miRNA-155KO mice lacking only 19 bp of the miRNA-155 core sequence without affecting the expression of lncRNA-155, as evidenced by faster body weight loss, poorer survival, and higher viral load, suggesting an additional role of lncRNA-155 in regulating viral pathogenesis besides via processing miRNA-155. Congruously, miRNA-155-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…MIR155HG plays a crucial role in regulating innate immunity, far beyond the processing of miR-155. Knockout mouse models lacking most of the MIR155HG sequences and another lacking the core miRNA-155 sequence showed that MIR155HG and miR-155 have distinct functions in immunity, with MIR155HG acting through IFN production and miR-155 acting through the regulation of the STAT1 signaling pathway [66]. While MIR155HG is a direct target of NF-κB that promotes its transcription [22], in a positive feedback mechanism, the MIR155HG/miR-155 axis also regulates NF-κB activity by interfering with its upstream elements or related signaling molecules and induces inflammation and the release of proinflammatory cytokines [67].…”
Section: Discussionmentioning
confidence: 99%
“…MIR155HG plays a crucial role in regulating innate immunity, far beyond the processing of miR-155. Knockout mouse models lacking most of the MIR155HG sequences and another lacking the core miRNA-155 sequence showed that MIR155HG and miR-155 have distinct functions in immunity, with MIR155HG acting through IFN production and miR-155 acting through the regulation of the STAT1 signaling pathway [66]. While MIR155HG is a direct target of NF-κB that promotes its transcription [22], in a positive feedback mechanism, the MIR155HG/miR-155 axis also regulates NF-κB activity by interfering with its upstream elements or related signaling molecules and induces inflammation and the release of proinflammatory cytokines [67].…”
Section: Discussionmentioning
confidence: 99%
“…Human lung epithelial cells (A549), human embryonic kidney cells (HEK293T/293T), mouse embryo fibroblast cells (NIH/3T3), murine lung epithelial-12 cells (MLE-12), mouse breast cancer cells (4T1), mouse lung adenoma epithelial-4 cells (LA-4), porcine kidney epithelial cells (PK-15), mouse mononuclear macrophage cells (RAW 264.7), chicken embryonic fibroblast cells (DF-1), and MDCK cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) (Gibco, Billings, MT) supplemented with 10% (vol/vol) fetal bovine serum (Gibco), 100 U/mL penicillin, and 100 U/mL streptomycin in 37°C incubator under humidified 5% CO 2 as previously described ( 48 ). Recombinant human IFN-β was purchased from PeproTech (PeproTech Inc., Rocky Hill, NJ), and poly(I:C), BAY 11-7082, and dimethyl sulfoxide (DMSO) were purchased from Sigma-Aldrich (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing evidence revealing that long noncoding RNAs (lncRNAs) play critical roles in regulating innate immunity and IAV pathogenesis [37][38][39]. To dissect the autophagy-independent mechanism by which ATG7 promotes the viral replication, we performed RNA-Seq to analyze differentially expressed lncRNAs between control and ATG7 knockdown A549 cells infected with influenza virus A/PR8/34 (H1N1) (Figs 6A and S6A).…”
Section: Identification Of Lncrna Gaplinc As a Critical Regulator Inv...mentioning
confidence: 99%